2016
DOI: 10.1111/pde.12777
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Herbal Medicine for Pediatric Lymphatic Malformations: A Pilot Study

Abstract: BackgroundLymphatic malformations (LMs) are congenital malformations of the lymphatic system that commonly affect the head and neck region and cause marked cosmetic and functional complications. In this pilot study, we present eight children with LMs treated using an herbal medicine for this indication.MethodsBetween January 2009 and May 2014, eight children (four boys, four girls) with LMs were treated using oral administration of an herbal medicine, Eppikajyutsuto (TJ‐28; Tsumura, Tokyo, Japan), as monothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Eppikajutsuto (TJ‐28), a Japanese herbal medicine, is reported to reduce redundant body fluids and have anti‐inflammatory effects . Our literature search revealed that TJ‐28 treatment led to the regression of lymphangiomas in 10 children; the locations included the head, neck, shoulder, chest, and retroperitoneum . The successful treatment of a mediastinal lymphangioma with TJ‐28 has only been reported in a 2‐year‐old boy, in whom the lesion showed marked regression after 9 months of treatment.…”
Section: The Reported Cases Of Prenatally Diagnosed Mediastinal Lymphmentioning
confidence: 99%
“…Eppikajutsuto (TJ‐28), a Japanese herbal medicine, is reported to reduce redundant body fluids and have anti‐inflammatory effects . Our literature search revealed that TJ‐28 treatment led to the regression of lymphangiomas in 10 children; the locations included the head, neck, shoulder, chest, and retroperitoneum . The successful treatment of a mediastinal lymphangioma with TJ‐28 has only been reported in a 2‐year‐old boy, in whom the lesion showed marked regression after 9 months of treatment.…”
Section: The Reported Cases Of Prenatally Diagnosed Mediastinal Lymphmentioning
confidence: 99%
“…The use of some traditional medicine formulations for treating pediatric surgical conditions has been reported . Ohya et al .…”
Section: Discussionmentioning
confidence: 99%
“…The herb ephedra is suggested to suppress of vascular endothelial growth factor activity by inhibiting prostaglandin E2 synthesis and cyclooxygenase protein synthesis, which might contribute to the shrinkage of LMs [7, 1012]. Hashizume et al reported the mean LM volume shrinkage rate of 54.5 ± 38.3% in eight patients who received the medicine [6].…”
Section: Discussionmentioning
confidence: 99%